2008
DOI: 10.1021/ol801708x
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Amphidinolide J

Abstract: The marine natural product amphidinolide J has been synthesized according to a convergent strategy. The key steps of this synthesis include a B-alkyl Suzuki-Miyaura coupling and the addition of an alkynyllithium reagent to a Weinreb amide to build the C4-C5 and C12-C13 bonds, respectively, and a Yamaguchi macrolactonization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…52 In addition to the case studies discussed above, many other instructive applications of the '9-methoxy-9-BBN variant' to the late-stage assembly of complex bioactive target molecules were reported in the literature (Table 2). This includes, inter alia, elegant partial or total syntheses of amphidinolide E, 53 amphidinolide J, 54 kendomycin, 55,56 iridal, 57 the haterumalides, 58 (putative) iriomoteolide-1a, 59-61 neopeltolide, 62 cordiaquinone K, 63 plakortone B, 64 and didemnaketal B. 46,65 Collectively, these examples illustrate the outstanding performance and functional group tolerance of the '9-MeO-9-BBN variant' of the Suzuki reaction, which is a mature and enabling methodology for natural product total synthesis.…”
Section: Mycolactonementioning
confidence: 99%
“…52 In addition to the case studies discussed above, many other instructive applications of the '9-methoxy-9-BBN variant' to the late-stage assembly of complex bioactive target molecules were reported in the literature (Table 2). This includes, inter alia, elegant partial or total syntheses of amphidinolide E, 53 amphidinolide J, 54 kendomycin, 55,56 iridal, 57 the haterumalides, 58 (putative) iriomoteolide-1a, 59-61 neopeltolide, 62 cordiaquinone K, 63 plakortone B, 64 and didemnaketal B. 46,65 Collectively, these examples illustrate the outstanding performance and functional group tolerance of the '9-MeO-9-BBN variant' of the Suzuki reaction, which is a mature and enabling methodology for natural product total synthesis.…”
Section: Mycolactonementioning
confidence: 99%
“…Moreover, disubstitution at C3, which hampered the thermal [2,3]-sigmatropic shift of cyclo­propenyl­carbinyl phosphonites, is well accommodated by the Ireland–Claisen rearrangement. It was observed that the rearrangement of 3a , although favored by the relief of ring strain, did not experience significant rate acceleration compared to regular allylic glycolates. , For a more meaningful comparison, the Ireland–Claisen rearrangement of glycolate 3b substituted by a styryl group was studied. After hydrolysis and esterification, analysis of the crude product by 1 H NMR spectroscopy indicated the exclusive formation of vinylcyclopropene 8 , which was isolated in 60% yield.…”
mentioning
confidence: 99%
“…The transformation of 3 to ( R )-hydroxyaldehyde 6 was achieved in 4 steps. After converting acetal 3 into ketone 4 by the addition of propynylmagnesium bromide (THF, −78 to 0 °C, 94%), the ketone was enantioselectively reduced by applying a Noyori asymmetric hydrogen transfer using Ts‑DPEN-RuCl­( p -cymene) I (10 mol %, i PrOH–CH 2 Cl 2 ) to produce 5 in 66% yield with an excellent ee (ee = 90%) . The reaction needed a high loading in Noyori’s catalyst (10 mol %) to increase the reaction rate, while at a lower loading (5 mol %) a competitive reduction of the triple bond was eroding the yields in the desired propargylic alcohol 5 .…”
Section: Results and Discussionmentioning
confidence: 99%